PEMBERDAYAAN KOMITE SEKOLAH DALAM MENINGKATKAN EFISIENSI PENGELOLAAN SEKOLAH DI KOTA DEPOK (Studi Kasus pada Komite SMAIT Al-Qudwah Kota Depok) - Marsofiyati Marsofiyati; Susan Febriantina (Fakultas Ekonomi Universitas Negeri Jakarta, 2016)
ABSTRACT This study aims to determine the school committee in an effort to empower SMAIT Al Qudwah Depok City in order to improve the efficiency of school management. This research was qualitative research site in SMAIT Al Qudwak Depok. The data source research is the principal, vice principal, school board committees as well as some students. Collecting data using the method of observation, interviews, documentation and archive footage, while the analysis of data using qualitative data analysis interactive model. The results showed that: (1) The Board committee at Al-Qudwah SMAIT Depok City consists of various professions and have a minimum education level Bachelor (S1); (2) Implementation of the program of work of the school committee in SMAIT Al Qudwah Kota Depok yet fully effective. It is characterized by not fahamnya school board committee will function and role of the school committee in improving the efficiency of school management in schools; (3) Empowerment committee at Al-Qudwah SMAIT Depok City has not fully maximized. It is characterized by the limited space of empowerment for the management committee of the school as a partner school. Besides, the school has not fully facilitate the school committee to explore the potential of its staff so that its existence can be empoweredKeywords: characteristics, role and functions, empowerment, school committees